Effectiveness of an online food shopping intervention to reduce salt purchases among individuals with hypertension – findings of the SaltSwitch Online Grocery Shopping (OGS) randomised trial - Jason HY Wu; Damian Maganja; Liping Huang; Kathy Trieu; Fraser Taylor; Eden M. Barrett; Clare Arnott; Xiaoqi Feng; Aletta E. Schutte; Gian Luca Di Tanna; Cliona Ni Mhurchu; Adrian J. Cameron; et al. (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Online grocery shopping is a growing source of food purchases in many countries. We investigated the effect of nudging consumers towards purchases of lower sodium products using a web browser extension. Methods This trial was conducted among individuals with hypertension who shopped for their groceries online in Australia. From July 2021 to June 2023, participants were randomised to use the SaltSwitch Online Grocery Shopping web browser extension or continue their usual grocery shopping for 12 weeks. The SaltSwitch extension modified a retailer’s online shopping interface to suggest similar but lower sodium alternative products to those initially selected. The primary outcome was the difference in mean sodium density (mg sodium per 1000 kcal of energy) of packaged food purchases between the intervention and control groups. Results We randomised 185 participants of average age 56.0 (SD 11.0) years. Most were women (64%), White (89%), had BMI > 25 kg/m2 (91%), and were taking anti-hypertensive medication (83%). Demographic and medical characteristics were similar across the randomised groups. 182 (98%) completed the trial. Over the 12-week intervention, the sodium density of groceries purchased by the intervention group compared to the control group was 204 mg/1000 kcal lower (95%CI, -352 to -56) (P = 0.01). The reduction in sodium density of purchases was apparent in weeks 1–4 and sustained through the end of the trial. 86% of participants in the intervention group made at least one switch to a lower sodium product. There were no detectable effects on blood pressure, spot urine sodium concentration, or other secondary outcomes across the 12-week study period. Conclusions Online shopping platforms provide a novel opportunity to support purchases of lower sodium foods. While the reductions in sodium density of purchases were moderate in size, population health benefits could nonetheless be large if they were sustained over time and at scale, with large and growing numbers of online grocery shoppers and a high prevalence of elevated blood pressure amongst adults. Trial registration ACTRN12621000642886.